Long-term functional results of orthotopic urinary derivation by Studer and VIP after radical cystectomy in women - V. A. Atduev; Yu. O. Lyubarskaya; D. S. Ledyaev; Z. K. Kushaev (Вестник урологии)
Introduction. The feasibility of reconstructing an orthotopic urinary reservoir after radical cystectomy (RCE) in women is still debatable. This is due to the peculiarities of the physiology and anatomy of the female lower urinary tract and an increased risk of developing urinary incontinence or urinary retention after surgery.Purpose of the study. Studying long-term functional results of creating an orthotopic urinary reservoir by VIP in comparison with the technique of creating a urinary reservoir by Studer after RCE in women.Materials and methods. The study included 32 women who underwent RCE with the formation of an orthotopic urinary reservoir by to Studer — 13 patients and a «spherical» reservoir in the VIP — 19 modification. At the time of surgery, the age of patients was 61.1±1.9 years (29 ‒ 82). The average follow-up time was 77.5±7.8 months (17 ‒ 157, median 82). The patients who underwent a more complex type of plastic were younger than the patients operated on by the Studer method (p = 0.014). The groups did not differ statistically in other parameters.Results. The overall five-year survival rate in the Studer group was 90.9%, and in the VIP group — 94.7% (p = 0.596). 59.4% of patients were completely continent. Women after plastic surgery by VIP held urine better (68.4% vs 46.2%). The incidence of mild urinary incontinence was higher after Studer surgery. The incidence of severe urinary incontinence was the same in both groups. Nighttime urinary incontinence was the same in both groups. Intermittent catheterization was used more often by patients after VIP plastic surgery than after Studer surgery (21% vs 7.7%). In urodynamic studies, it was shown that the lower physiological capacity of the reservoir according to Studer due to more intense peristalsis of the reservoir wall, which causes involuntary leaking of urine, hyperperistalsis of the reservoir and a higher frequency of urinary incontinence causes more complete emptying in patients less residual urine, less need for self-catheterization. In the group of patients with plastic surgery according to VIP, a high physiological capacity of the reservoir with a lower pressure of the walls of the reservoir during the filling phase was recorded. This is manifested by a lower incidence of urinary incontinence, and, at the same time, a more significant amount of residual urine and a higher need for patients for self-catheterization.Conclusion. The formation of an orthotopic urinary reservoir with favourable long-term results is possible in women after RCE. The most beneficial in terms of the quality of daily held urine is the VIP modification, which is characterized by sufficiently high capacity and low intraluminal pressure. However, with this method of surgery, the risk of hypercontinence increases, which requires periodic catheterization. A complex urodynamic study made it possible to show the direct effect of various characteristics of the reservoir on the nature and degree of impaired urination of patients.